ANALISIS ILUSTRASI BARONG PADA MEDIA PROMOSI JAVA JAZZ 2015 - Teuku Giara Gaesaro Syah; Elda Franzia Jasjfi (Universitas Trisakti, 2017)
AbstractThe development of music industry marked by the increasing number of the music event held nowadays. In terms of music festival that was held every year, the development of updates in social media which help publish those events. One of the biggest event held annually is Java Jazz Festival. Java Jazz Festival 2015 with the theme